Action planning and coping planning based intervention on physical activity practice among desk-based office employees: a non-randomized explanatory mixed method study - Nambirajan, Murali Krishnan; Govindan, Dhanajayan; Patel, Namita; Roy, Gautam; Lakshminarayanan, Subitha (International Journal Of Community Medicine And Public Health, 2022)
Background: Desk-based office workers have sedentariness in the workplace due to the nature of their work. So we aimed to determine the effect of action planning and coping planning based physical activity intervention among participants and explore its utility. Methods: This study was conducted among office staff employed in six to eight hours of desk- based office work of JIPMER, Puducherry during November 2020 to January 2021. Simple random sampling of employees from available database was done to select 150 participants based on inclusion criteria. Intervention was individual specific action and coping planning for physical activity (PA). Change in the level of PA and its stage, body composition parameters and step-counts were measured at end-line to assess the effect of intervention supported by the qualitative interviews. Results: An adequate level (≥600 METS) of physical activity among participants in the intervention group increased by 42% among Total MET minutes spent (p<0.001). Muscle mass improved in the intervention arm by 4% (p>0.001). Conclusions: Implementation plan is effective in improving the physical activity level of the participants and adopting healthy PA behaviour and advocates for health promoting workplace.